Energy and Exergy Analysis on Modified Closed Wet Cooling Tower in Iraq - Mahdi, Qasim Saleh; Jaffal, Hayder Mohammad (Al-Khwarizmi Engineering Journal, 2017)
The present study involves experimental analysis of the modified Closed Wet Cooling Tower (CWCT) based on first and second law of thermodynamics, to gain a deeper knowledge in this important field of engineering in Iraq. For this purpose, a prototype of CWCT optimized by added packing under a heat exchanger was designed, manufactured and tested for cooling capacity of 9 kW. Experiments are conducted to explore the effects of various operational and conformational parameters on the towers thermal performance. In the test section, spray water temperature and both dry bulb temperature and relative humidity of air measured at intermediate points of the heat exchanger and packing. Exergy of water and air were calculated by applying the exergy destruction method on the cooling tower. Experimental results showed a significant performance improvement when using packing on the CWCT. It can be observed that the thermal efficiency for the CWCT with packing under a heat exchanger and CWCT with packing above the heat exchanger are approximately 40% and 25% higher than that of the CWCT without packing respectively. As another part of the experiment results, it is indicated that the exergy destruction is directly proportional to air flow rate, cooling water flow rate, inlet cooling water flow rate and inlet Air Wet Bulb Temperature (AWBT) whereas, it is inversely proportional with spray water flow rate. In comparison with the cooling capacity of the tower, it was found that the exergy destruction approximately less than 20%. Exergy efficiency behavior is inversely proportional with the behavior of the exergy destruction. Empirical correlations are obtained to predict water film heat transfer coefficient and air-water mass transfer coefficient considering the influences of operational parameters.